"A Common Danger Unites": Reflecting on Lecturers' Higher Education Experiences during the COVID-19 Pandemic Using an Ethnographic Fictional Analysis - Gerald Griggs; Helen J. Heaviside (MDPI AG, 2023)
The sudden transition of Higher Education (HE) from predominately face-to-face to online delivery during the COVID-19 pandemic lockdowns placed many lecturers in unfamiliar situations. This study aimed to explore and represent the experiences of lecturers working in HE during this time. We used a storytelling approach to represent an amalgamation of experiences collated from lecturers. Data were collected using (i) a focus group interview, (ii) reflections on our experiences, and (iii) experiences alluded to by academics via online blogs. The data were presented using an ethnographic fiction. Salient experiences detailed throughout the ethnographic fiction include (i) challenges building a community between colleagues, academics, and students; (ii) concerns regarding the capacity of institutions and staff to deliver online; (iii) a lack of synergy between the expectations of staff to fulfil duties and the reality of being able to do so in time; (iv) the challenges of engaging students; (v) concerns regarding the accessibility of online learning for a diverse body of students; and (vi) challenges with work-life balance. The ethnographic fiction provides a voice for HE lecturers who candidly shared their experiences of working during the pandemic. Stakeholders are encouraged to develop their own interpretations of the story and apply these to policy and practice.